The Communication Style of the Host on Meet Nite Live Program - Pagi Muhamad (Dinasti International Journal of Education Management And Social Science, 2024)
This study explores the communication style of Valentinus Resa, the host of the Indonesian infotainment program Meet Nite Live, and its impact on audience engagement and the perception of news content. The program blends critical news commentary with humor and satire and uses a distinctive communication approach to attract and engage a younger, digitally savvy audience. Research highlights how Resa’s informal, conversational style contrasts with traditional formal news delivery, fostering greater viewer relatability and engagement. Through qualitative content analysis, this study examines Resa’s verbal and nonverbal communication techniques, including humor, tone, body language, and audience interaction via social media. Findings indicate that these techniques enhance audience connection, making serious news topics more accessible and engaging without diminishing their credibility. Humor and satire, especially in political commentary, encourage critical thinking and facilitate viewer reflection on social and political issues. The research further demonstrates the effectiveness of media convergence, where interactive and rich media environments strengthen audience participation. The results offer insights into how modern infotainment balances entertainment and information, underscoring the importance of adapting communication styles to contemporary media consumption patterns.